ISSUES OF RISK MANAGEMENT IN INNOVATIVE ENTREPRENEURSHIP, ENSURING ITS STABILITY AND SECURITY - Yuldashbayev, Azizullokh (THE INNOVATION ECONOMY, 2026)
The study examines the issues of ensuring the stability and security of the innovative entrepreneurship system based on managing the impact of various risks, threats, and hazards that arise in the processes of its formation and development.